1993
DOI: 10.1007/bf00027185
|View full text |Cite
|
Sign up to set email alerts
|

Screening techniques and sources of tolerance to salinity and mineral nutrient imbalances in cool season food legumes

Abstract: A large global land area is affected by saline, alkali (sodic), and acid soil conditions . Cool season food legumes are important crops in many countries with such adverse soils . Tolerant genotypes have been identified in many crops, including legumes. However, very little has been published on selection of tolerant cool season food legume crops . The inadequate knowledge and understanding of the responses of cool season food legume crops to these abiotic stresses, necessitates action by a collaborative netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…1998), but acts as a protective agent against cellular damage. Screening of chickpea cultivars on the basis of proline accumulation in young plants has given inconsistent results (Chandra 1980, cited in Saxena et al. 1994), suggesting that it is not related to salinity resistance in chickpea.…”
Section: Vegetative Growthmentioning
confidence: 99%
“…1998), but acts as a protective agent against cellular damage. Screening of chickpea cultivars on the basis of proline accumulation in young plants has given inconsistent results (Chandra 1980, cited in Saxena et al. 1994), suggesting that it is not related to salinity resistance in chickpea.…”
Section: Vegetative Growthmentioning
confidence: 99%
“…For field pea, relatively high and heritable genetic tolerances to Fe deficiency [29] and boron toxicity [30-32] have been identified. In terms of salinity tolerance, preliminary studies based on biomass reduction indicated that field pea is significantly more sensitive than other commonly cultivated Australian broad-acre crops such as barley [33,34], wheat [35] and canola [36], due to a low salinity threshold level [37] in pea. In comparison to other legumes, in contrast, pea [38-41], as well as faba bean [42], appear more tolerant than chickpea [43] and lentil [44].…”
Section: Introductionmentioning
confidence: 99%
“…Yield losses due to Fedeficiency in susceptible chickpea genotypes can be in the range 22-50% (Saxena et al, 1994). Literature on the effects of alkaline soil conditions (high pH, calcareous soils), appearance of Fe-chlorosis, yield losses due to deficiency, genotypic differences in Fedeficiency and its inheritance, screening methods, and criteria for selection have been reviewed by Saxena et al (1994). Good progress has been made in understanding the physiological basis of development of Fe-deficiency.…”
Section: Ironmentioning
confidence: 99%
“…Responses of cool season food legumes (including chickpea), to salinity, methods to screen for tolerance to saline conditions, inheritance of the trait, and genotypic differences in tolerance, have been reviewed (Saxena et al, 1993(Saxena et al, , 1994. The levels of tolerance to soil salinity are indeed low in chickpea as seen in a 50% reduction in shoot biomass at an electrical conductivity (EC) of 5-6 dS m −1 .…”
Section: Salinitymentioning
confidence: 99%